THE IMPORTANCE OF DEVELOPING PRIMARY SCHOOL PUPILS’ SPEECH - Xurramova Aziza Abdurasul qizi (International Journal of Literature and Language Studies, 2026)
Abstract: The family, preschool educational institutions, and, above all, school education play an important role in developing children’s correct, fluent, meaningful, and expressive speech. This article examines the concept of speech development, the current state of primary school pupils’ speech, and the forms and means of developing oral and written speech in native-language and reading-literacy lessons. Particular attention is paid to the use of non-traditional teaching methods, didactic materials, creative tasks, literary works, and didactic games. The article also discusses the opportunities provided by textbooks developed on the basis of the National Curriculum for improving pupils’ independent thinking, vocabulary, coherent speech, and ability to express their ideas clearly.